Synthesis and Crystal Structure of phen2Co-2N3 - Bi, Jian-Hong; Ding, Rong-Jin; Huang, Zi-Xian; Chen, Yan; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A novel cobalt complex phen2Co-2N3, where phen is 1,10- phenanthroline, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is triclinic, space group P-1 with unit cell parameters: a = 8.090 Å, b = 12.7351 (5) Å, c = 14.2705 (3) Å, α = 82.912 (15)º, β = 73.595(16)º, γ = 72.122(13)º, V = 1341.22 (6) Å3, Z = 2, Mr = 543.93, Dc = 1.347 Mg/cm3, μ = 0.681 mm-1, F(000) = 559, T = 293(2)K, R = 0.0782, wR = 0.2482 for 10293 reflections with I > 2σ(I). The crystal structure analysis shows that the Co(II) is a six-coordinated in a slightly distorted octahedron environment.